Margaret Conrad: Planter and Loyalist Contributions - Davies, Gwendolyn (Atlantis, 2010)
This paper examines Margaret Conrad's central contributions to the fields of Planter and Loyalist Studies, underlining her combination of originality in research and commitment to making this history accessible to the general public.